(untitled) (Nepal Medical College Journal, 2023)
Acne is a disease involving pilosebaceous unit commonly affecting adolescents. Acne has a multifactorial aetiology but in recent years, studies have shed some light in the relationship between cigarette smoking and acne. As previous studies linking cigarette smoking and acne had produced conflicting results, we conducted this study to provide comprehensive information of cigarette smoking and its association with acne in Nepalese population. The study comprised all participants who met the inclusion criteria as well as a control group that was age and sex matched. The demographic profile, smoking history, previous history, drug history, and examination results were entered into a pre-set proforma. There were a total of 100 cases of acne patients (Group A) with age and sex-matched 100 controls (Group B). There were 69% females and 31% males. The majority of the acne patients (Group A) were students in 65%, as compared to 42% in control group. In group A, 95% never smoked and 5% were smokers (cigarettes). In group B, 98% never smoked and 2% were smokers (cigarettes). The commonest site of acne lesions was in face 64. Among the acne patients there were 27% mild acne, 58% moderate acne and 15% severe acne. There was no association found between cigarette smoking and acne (OR- 2.57, 95% CI -0.4884 to 13.6173, P>0.05). There was no correlation between acne and smoking in Nepalese population. However, a larger sample size is recommended to confirm the correlation.